Pengaruh Struktur Kepemilikan dan Struktur Modal terhadap Kebijakan Dividen dengan Nilai Perusahaan sebagai Variabel Moderasi - Nela Nur Faridah; Rediyanto Putra (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was conducted to determine the influence of managerial ownership, institutional ownership, capital structure and company value on dividend policy as well as the moderating influence of company value on the relationship between managerial ownership, institutional ownership and capital structure and dividend policy. Based on quantitative research methods with purposive sampling techniques, 10 manufacturing sector companies in the consumer goods industry sub-sector were obtained on the IDX in the 2018-2022 period. The research results show that there is an influence between institutional ownership, capital structure and company value on dividend policy, while managerial ownership has not been able to influence dividend policy, and company value can moderate the relationship between institutional ownership and capital structure on dividend policy.